2008
DOI: 10.1016/j.otohns.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of surgeon‐performed ultrasound‐guided thyroid fine‐needle aspiration biopsy

Abstract: Prior publications recommend that obtaining adequate thyroid cytology specimens requires use of US-guided FNAB and on-site evaluation of cytology adequacy. This study demonstrates that a combination of experienced US guidance, both capillary and aspiration sampling, and three to four needle passes produce comparable results while conserving costs and resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 15 publications
4
52
0
2
Order By: Relevance
“…As reported by Ljung et al [13], the nondiagnostic rate in 314 breast FNAB performed by physicians without specific training was 36.9% compared with 2.2% in 729 FNAB performed by adequately trained physicians. Bhatki et al [14] also reported an 8.2% rate of nondiagnostic thyroid US-FNAB performed by an inexperienced radiologist compared with 5.4% performed by an expert radiologist. Because the training of young radiologists is key to the success of the procedure, the biopsy should be done under the supervision of an expert radiologist.…”
Section: Discussionementioning
confidence: 96%
See 1 more Smart Citation
“…As reported by Ljung et al [13], the nondiagnostic rate in 314 breast FNAB performed by physicians without specific training was 36.9% compared with 2.2% in 729 FNAB performed by adequately trained physicians. Bhatki et al [14] also reported an 8.2% rate of nondiagnostic thyroid US-FNAB performed by an inexperienced radiologist compared with 5.4% performed by an expert radiologist. Because the training of young radiologists is key to the success of the procedure, the biopsy should be done under the supervision of an expert radiologist.…”
Section: Discussionementioning
confidence: 96%
“…Come riportato infatti da Ljung et al [13], la percentuale non-diagnostica in 314 FNAB mammarie eseguite da medici senza uno specifico training era del 36,9% rispetto al 2,2% in 729 FNAB dei medici formati con adeguato training. Anche Bhatki et al [14] hanno riportato una percentuale di FNAB-ecoguidate tiroidee non diagnostiche dell'8,2% del radiologo inesperto rispetto al 5,4% del radiologo esperto. Costituendo pertanto il training del giovane radiologo un aspetto fondamentale della procedura, esso deve essere condotto sotto la supervisione di un radiologo esperto e dovrebbe constare inizialmente di un periodo di esclusiva osservazione per valutare l'importanza dell'indicazione e della fattibilità dell'esame e non ultimo per affinare la capacità nella gestione e nella comunicazione con il paziente.…”
Section: Discussioneunclassified
“…9,[11][12][13][14][15][16][17][18][19] It has been recommended that in order to maintain satisfactory standards, US-FNABs should be carried out by dedicated groups of clinicians. 20,21 Our series demonstrated that with appropriate training, thyroid surgeons are well placed to perform such procedures in the office setting due to their sound understanding of the anatomy and pathology of thyroid gland, and their considerable experience gained from large caseload numbers of patients with thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the number of separate passes used should be based on whether on-site assessment of cytology is available, and whether additional studies are planned. In the absence of on-site adequacy assessment, the preferred number is three to four passes (27).…”
Section: Ultrasound-guided Fine-needle Aspiration Of Cervical Lymph Nmentioning
confidence: 99%
“…We recommend attempts to focus preoperative evaluation at high volume centers for radiological evaluation, as the diagnostic performance of staging ultrasound for thyroid malignancy varies according to experience (27,39).…”
Section: Ultrasound Expertisementioning
confidence: 99%